Frustrated Lewis Pair Catalyzed Dehydrogenative Oxidation of Indolines and Other Heterocycles - Maier, Alexander F. G.; Tussing, Sebastian; Schneider, Tobias; Flörke, Ulrich; Qu, Zheng-Wang; Grimme, Stefan; Paradies, Jan (Angewandte Chemie International Edition, 2016)
An acceptorless dehydrogenation of heterocycles catalyzed by frustrated Lewis pairs (FLPs) was developed. Oxidation with concomitant liberation of molecular hydrogen proceeded in high to excellent yields for N‐protected indolines as well as four other substrate classes. The mechanism of this unprecedented FLP‐catalyzed reaction was investigated by mechanistic studies, characterization of reaction intermediates by NMR spectroscopy and X‐ray crystal analysis, and by quantum‐mechanical calculations. Hydrogen liberation from the ammonium hydridoborate intermediate is the rate‐determining step of the oxidation. The addition of a weaker Lewis acid as a hydride shuttle increased the reaction rate by a factor of 2.28 through a second catalytic cycle. The acceptorless dehydrogenation of N‐protected indolines and other heterocycles is catalyzed by frustrated Lewis pairs. Mechanistic as well as quantum‐mechanical studies revealed the liberation of molecular hydrogen to be the rate‐determining step. The addition of a weaker Lewis acid as a hydride shuttle increased the reaction rate by a factor of 2.28.